Determinants of Non-Performing Loans in Rural Banks: Evidence from South Sumatra, Indonesia - Prirayani, Jagat (Jurnal Sosial Teknologi, 2025)
This study investigated the factors influencing the emergence of Non-Performing Loans (NPL) at Rural Banks in Southern Sumatra, one of the western provinces of Indonesia, from the perspective of debtors. The data were gathered through questionnaires distributed to 285 debtors with non-performing credit across the province. The questionnaire utilized an ordinal scale from 1 to 10. It included 15 variables: Length of Procedure, Officer Capacity, Credit Monitoring, Business Appraisal, Credit Period, Principal Amount, Interest Rate, Interest Rate Change, Customer Appraisal, Debtor Relations, Collateral Appraisal, Credit Allocation, Money Recording, Business Competition, and Economic Condition. The data were processed using Factor Analysis. Using factor analysis as the primary method, the study reduces the factors into three general factors and found that non-performing loans in the region are affected by the linear combination of the observed variables.